Institutionalisation by Proxy: The (Re)construction of My Relationship as a Granddaughter. Issue 3 (3rd July 2022) - Shaw, Susan
ABSTRACT: Supporting older family members can be complex and involve navigating service providers, funding agencies and individual practitioners along with personal, social and emotional challenges. This paper presents insights into my lived experience as a granddaughter throughout the journey of my grandmother moving from the community into a residential care facility. Despite my intellectual and professional understanding of many of the issues and complexities the journey has been difficult and has ultimately changed my relationship as a granddaughter. Moments of this journey reflected in emails and diary notes are presented along with a critical consideration of the personal and ethical issues. My hope is to provide some insights into how residential services can impact fundamental social dynamics within a family, effectively extending the institutionalisation beyond those who enter care.